Exile and cultural hegemony : Spanish intellectuals in Mexico, 1939-1975 - Faber, Sebastiaan, 1969- (Vanderbilt University Press, 2002)
Places the exiles' ideological evolution in a broad historical context and takes into account developments in both Spanish and Mexican politics from the early 1930s through the 1970s.